Kelekatan dalam Perkembangan Anak - Zusy Aryanti (Tarbawiyah Jurnal Ilmiah Pendidikan, 2015)
Attachment is strong relationship between achild and his mother or nanny due to the intensive interaction. It is becoming an important aspect as the base of children’s psychological development, because it gives children an opportunity to explore the environment comfortably. Child with a good attachment to their parent will posses a positive psychological development, such as feeling safe, being able to explore, working model of their reviving relationship, being conficeent, developing his intellectual potential, being capable of thinking logically, being capable of developing his emphaty, being capable of coping with stress and frustration, being capable of coping with fear and anxiety as well as being capable of developing a good social relationship with other people.